2018
DOI: 10.1371/journal.pone.0194045
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Daphnia magna Straus (Crustacea: Cladocera) in Northern Eurasia: Evidence for a deep longitudinal split between mitochondrial lineages

Abstract: Species with a large geographic distributions present a challenge for phylogeographic studies due to logistic difficulties of obtaining adequate sampling. For instance, in most species with a Holarctic distribution, the majority of studies has concentrated on the European or North American part of the distribution, with the Eastern Palearctic region being notably understudied. Here, we study the phylogeography of the freshwater cladoceran Daphnia magna Straus, 1820 (Crustacea: Cladocera), based on partial mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 97 publications
4
49
0
Order By: Relevance
“…Evidence of their existence in the Beringian region in the Pleistocene could be also obtained from their phylogeography: for instance, Daphnia (C.) magna now has a disrupted distribution area, being recorded from Eurasia and North America, but not in NE to Central Yakutia and NW Canada. It is likely that this recent biogeographic pattern has appeared as a result of the disjunction of a single pan-Beringian distribution area 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of their existence in the Beringian region in the Pleistocene could be also obtained from their phylogeography: for instance, Daphnia (C.) magna now has a disrupted distribution area, being recorded from Eurasia and North America, but not in NE to Central Yakutia and NW Canada. It is likely that this recent biogeographic pattern has appeared as a result of the disjunction of a single pan-Beringian distribution area 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Microcyclops varians (Sars, 1863) 1 1 0 1 1 1 1 0 0 Paracyclops fimbriatus orientalis (Alekseev, 1995) 1 Based on genetic data, it was concluded that there is a main longitudinal biogeographic transitory zone between two faunistic super-complexes in the Yenisey River basin (sometimes in the Ob River basin) [Bekker et al, 2016[Bekker et al, , 2018Kotov et al, 2016], as it was predicted earlier [Korovhinsky, 2004]. Only three cladocerans (Sida ortiva, Diaphanosoma amurensis, Camptocercus uncinatus) from Lake Bolon basin belong to the Eastern Asian complex to date, but after revisions of particular taxa such number should be strongly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the methods of genosystematics in some cases makes it possible to identify a significant number of cryptic species, for example, both from poorly studied and extremely diverse coral fish [Hubert et al, 2012], and among seemingly well-morphologically studied aquatic invertebrates . On the other hand, there are hydrobionts, for example, the sea bass Sebastes from the North Atlantic well-differing both in terms of morphology and ecology but demonstrating extremely low genetic differentiation [Artamonova et al, 2013], whereas Daphnia magna crustacean, possesses extremely high intraspecific genetic diversity [Bekker et al, 2018], often exceeding even the intergeneric limits in other animals. A study of the genetic diversity of fish in North America also revealed the limitations of successful species identification using DNA analysis [April et al, 2011].…”
Section: Discussionmentioning
confidence: 99%